An analysis of physical activity coping plans: mapping barriers and coping strategies based on user ratings - Maya Braun; Geert Crombez; Femke De Backere; Emma Tack; Annick L. De Paepe (Health Psychology and Behavioral Medicine)
Introduction: Personalising recommendations for physical activity coping plans can help bridging the physical activity intention-behaviour gap. Data-driven ‘black-box’ approaches result in recommendations that prove difficult to explain, and may have undesired consequences. This study aimed to explicitly link barriers and coping strategies using end-user input.Method: 152 participants (85 female) took part in an online task. Participants were asked to judge the relevance of coping strategies for barriers to physical activity, and under which circumstances coping strategies were relevant for a given barrier. Data was aggregated and heat maps were produced. Necessary conditions for the relevance of each combination were coded and their frequencies were reported.Results: Relevance of 1570 combinations of barriers and coping strategies were assessed, with 2 combinations rated ‘always relevant’ by all participants, and 37 combinations rated as ‘always relevant’ by no participants. Barriers differ strongly in how many coping strategies are relevant for them, and coping strategies differ strongly in how many barriers they are relevant for. Resulting aggregates concerning the average rating as ‘never relevant’, ‘always relevant’ and ‘relevant under certain conditions’ are shared for each barrier coping strategy combination, as are the conditions associated with different barriers and coping strategies.Discussion: This study introduces a novel method to create rules for recommendations using input from stakeholders. The datasets created throughout this research are available for re-use in future research, as well as for clinical practice and (digital) intervention development. This data can be used as a base for explainable personalised recommendations for physical activity coping plans.